Examining the effects of negative emotion and interviewing procedure on eyewitness recall. Issue 1 (6th January 2022) - Snow, Mark D.; Eastwood, Joseph
Abstract: Witnessing or experiencing a crime can be emotionally distressing and this emotional reaction can affect the formation and retrieval of event‐related memory. Extant eyewitness research, however, has generated inconsistent conclusions regarding the effects of emotional arousal on eyewitness memory. In the planned study, we will use a mock witness paradigm to attempt to remedy several methodological limitations that have persisted in the literature and shed light on the effects of emotional memory within an investigative interviewing context. Participants will view either a negative or neutral video and either immediately or 1 week later provide their account of the video in a virtual interview procedure, consisting of either cognitive interview‐based instructions or a free recall. We will test the main effects of emotional arousal, interview procedure, and delay as well as their interactions. The present research will help clarify the nature of emotional memory in forensic contexts.